Linguistic-conceptual analysis of silence in the novel «Ivan» by V.O. Bogomolov - Licari, Camilla (Bulletin of Yerevan University H: Russian Philology, 2023)
A review of the verbal and nonverbal representations of the concept of silence and its cognitive and propositional structure in the literary context is presented in this paper. The research is based on the novel "Ivan" (1957) by Vladimir O. Bogomolov and the aim is to decode the general linguistic layer underlying the literary concept of silence and to discover the author's intention in the linguistic means of objectifying the concept. Using the pragmatic expressive and aesthetic approach typical of a literary text, the author narrates the mysterious story of Ivan, a twelve-year-old boy found in the water near the riverbank and arrested on suspicion of espionage. By employing the metaphor of silence, the author focuses on describing the boy's private history, deprived of his childhood, which he reverently guards in his silence, devoting more attention to that than to the depiction of military episodes. The article deals with a variety of verbalizations of the conceptual content of silence, revealing the author's individual perceptions of it, allowing him to present the conceptosphere of silence as a field, the core of which is a generalized cognitive and propositional structure that includes the main lexical representations of the concept. Figurative meanings constitute the immediate periphery, while subjective-modal meanings are the further periphery. Such an analysis helps to reveal the functions of the concept in focus and, consequently, to interpret the individual-authorial image of the world and broaden the understanding of the narrative text itself.